Ethanol and Xylitol Co-Production by Clavispora lusitaniae Growing on Saccharified Sugar Cane Bagasse in Anaerobic/Microaerobic Conditions - David Guzmán-Hernández; Ana C. Ramos-Valdivia; Héctor Mario Poggi-Varaldo; Josefina Barrera-Cortés; Eliseo Cristiani-Urbina; Teresa Ponce-Noyola (Fermentation, 2025)
Ethanol and xylitol are valuable bioproducts synthesized by non-conventional yeasts from lignocellulosic sugars. However, their biosynthesis requires distinct cultivation conditions. This study evaluated the production of ethanol and xylitol by Clavispora lusitaniae using saccharified sugarcane bagasse (SSCB) under three aeration conditions: microaerobic (C1), anaerobic (C2), and a combination of anaerobic followed by a microaerobic phase (C3). Ethanol production was maximum under anaerobic conditions (C2), followed by combined anaerobic–microaerobic conditions (C3). Meanwhile, xylitol production was most efficient under microaerobic conditions (C1). Notably, anaerobic conditions were ineffective for xylitol production. Enzyme activities of xylose reductase (XR) and xylitol dehydrogenase (XDH), key enzymes in xylose metabolism, were highest under microaerobic conditions with activities of 2.88 U/mg and 1.72 U/mg, respectively, after 48 h of culture. Gene expression analysis of XYL1 and XYL2 correlated with the corresponding enzyme activities (XR) and (XDH) with increased levels of 32.38 and 7.88 fold, respectively, compared to the control in C1. These findings suggest that C. lusitaniae co-produces ethanol efficiently under anaerobic conditions, while xylitol biosynthesis is optimized under microaerobic conditions when using xylose-rich saccharified lignocellulosic substrates.